HUBUNGAN PERSEPSI DENGAN KESIAPSIAGAAN BENCANA PADA TENAGA KESEHATAN - Susila, I Made Dwie Pradnya; Udaksana, I Made Adi Wahyu; A?ini, Nur (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Background Indonesia is a country which is frequently to natural disasters, geographically located between two continents and the plate of fire. Badung Regency is the main entrance of tourists to Bali so that the population movement in Badung Regency is very high. Badung Regency is recorded as the highest contributor to disasters in Bali Province so disaster preparedness is needed to reduce casualties and material losses. Objectives This study aims to determine the relationship of perception with disaster preparedness in village ambulance health workers. Method Cross sectional survey was conducted on 49 village ambulance health workers who were selected in total sampling in the working area of ??Petang and Abiansemal Districts. Data collection was conducted in May 2019 using a questionnaire. Data analysis was performed univariate, bivariate with chi square and multivariate with binary logistic regression. Results The results showed that only 42.9% of health workers had high levels of disaster preparedness. Perceived benefits related to disaster preparedness (AOR = 16.1; 95% CI: 1.83-141.35). Conclusion The perception of benefits is related to disaster preparedness.